Biochemical studies on antibiotic production from Streptomyces sp.: Taxonomy, fermentation, isolation and biological properties - Houssam M. Atta (Journal of Saudi Chemical Society)
Tunicamycin is a nucleotide antibiotic which was isolated from the fermentation broth of a Streptomyces strain No. T-4. According to the morphological, cultural, physiological and biochemical characteristics, and 16S rDNA sequence analysis, strain T-4 was identified as Streptomyces torulosus. It is active in vitro against some microbial pathogenic viz: Staphylococcus aureus, NCTC 7447; Micrococcus lutea, ATCC 9341; Bacillus subtilis, NCTC 10400; B. pumilus, NCTC; Klebsiella pneumonia, NCIMB 9111; Escherichia coli, NCTC 10416; Pseudomonas aeruginosa, ATCC 10145; Saccharomyces cerevisiae ATCC 9763; Candida albicans, IMRU 3669; Aspergillus flavus, IMI 111023; Aspergillus niger IMI 31276; Aspergillus fumigatus ATCC 16424; Fusarium oxysporum; Rhizoctonia solani; Alternaria alternata; Botrytis fabae and Penicillium chrysogenium. The production media were optimized for maximum yield of secondary metabolites. The metabolites were extracted using n-butanol (1:1, v/v) at pH 7.0. The chemical structural analysis with UV, IR, and MS spectral analyses confirmed that the compound produced by Streptomyces torulosus, T-4 is tunicamycin antibiotic.